Exploring factors that influence COVID-19 vaccination intention in China: Media use preference, knowledge level and risk perception - Chen, Xuejiao; Liu, Yuhan; Yu, Guoming (Frontiers in Psychology, 2022)
Vaccine is one of the most effective means to deal with the COVID-19 pandemic in many countries, but vaccine hesitancy has been always widespread among people due to individual differences in access to vaccine information. This research aims to empirically investigate the relationship between media use preference (video-based and text-based), knowledge level, risk perception and willingness to vaccinate among Chinese residents. A cross-sectional survey of a Chinese sample (N=885) was carried out to explore factors that influence the COVID-19 vaccination intention of Chinese residents. The empirical results show that the knowledge level and risk perception of Chinese residents positively contribute to vaccination intention. People with video-usage preference have lower levels of knowledge about the COVID-19 vaccine than those with text-usage preference. People’s risk perception of the COVID-19 pandemic is not influenced by their media use preference or knowledge level, as COVID-19 is a global pandemic and a significant social risk. The current study yields health-related implications for the role of media use preference in vaccination intention.